Clinical Data on Daptomycin plus Ceftaroline versus Standard of Care Monotherapy in the Treatment of Methicillin-Resistant Staphylococcus aureus Bacteremia - Geriak, Matthew (Antimicrob Agents Chemother, 2019)
Vancomycin (VAN) and daptomycin (DAP) are approved as a monotherapy for methicillin-resistant Staphylococcus aureus (MRSA) bacteremia. A regimen of daptomycin plus ceftaroline (DAP+CPT) has shown promise in published case series of MRSA salvage therapy, but no comparative data exist to compare up-front DAP+CPT head-to-head therapy versus standard monotherapy as an initial treatment. In a pilot study, we evaluated 40 adult patients who were randomized to receive 6 to 8 mg/kg of body weight per day of DAP and 600 mg intravenous (i.v.) CPT every 8 h (q8h) (n = 17) or standard monotherapy (n = 23) with vancomycin (VAN; dosed to achieve serum trough concentrations of 15 to 20 mg/liter; n = 21) or 6 to 8 mg/kg/day DAP (n = 2). Serum drawn on the first day of bacteremia was sent to a reference laboratory post hoc for measurement of interleukin-10 (IL-10) concentrations and correlation to in-hospital mortality. Sources of bacteremia, median Pitt bacteremia scores, Charlson comorbidity indices, and median IL-10 serum concentrations were similar in both groups. Although the study was initially designed to examine bacteremia duration, we observed an unanticipated in-hospital mortality difference of 0% (0/17) for combination therapy and 26% (6/23) for monotherapy (P = 0.029), causing us to halt the study. Among patients with an IL-10 concentration of >5 pg/ml, 0% (0/14) died in the DAP+CPT group versus 26% (5/19) in the monotherapy group (P = 0.057). Here, we share the full results of this preliminary (but aborted) assessment of early DAP+CPT therapy versus standard monotherapy in MRSA bacteremia, hoping to encourage a more definitive clinical trial of its potential benefits against this leading cause of infection-associated mortality. (The clinical study discussed in this paper has been registered at ClinicalTrials.gov under identifier NCT02660346.)